Problematika Dan Implikasi Omnibus Law Cipta Kerja Pada Perseroan Terbatas - Krista Yitawati; Anik Tri Haryani; Subadi; Adilla Nila Krusita (YUSTISIA MERDEKA : Jurnal Ilmiah Hukum, 2022)
Abstract— Despite the various controversies, the presence of the Omnibus Law on Job Creation have repealed at least two regulations and changed at least 80 (eight twenty) other laws. One of those affected is the Law Number 40 of 2007 concerning Limited Liability Companies (UU PT). Study This study intends to examine what the existing concepts and problems look like on the Omnibus Law on Job Creation, as well as its implications for the regulation and the basic concept of a Limited Liability Company. This study is a normative research (doctrinal) to secondary data obtained from literature studies (library research), which consists of primary and secondary legal materials. Research result shows that the Omnibus Law is a legislative method by unites various types of laws into one specific law. This has the potential to negate the diverse interests of each laws in the name of one interest only. In addition, the practice of drafting it in Indonesia does not have a juridical basis and violates the principle of openness and participation. In terms of its implications for the PT Law, a number of the provisions in the Omnibus Law on Job Creation have expanded the meaning of the Company Limited by presenting the Sole Proprietorship model which gives birth to a number of contradictions in the basic concept of a Limited Liability Company, in addition to removing the minimum capital limit of the Company which is feared will cause vulnerabilities for business continuity.